Parliament in the European style? An examination of the National Assembly of the Republic of Albania in light of the European Commission’s enlargement reports - Tóth, Lili (POLARITIES, 2026)
In 2022, the European Union reevaluated its enlargement strategy. In the Western Balkans, Bosnia and Herzegovina was granted candidate status, while accession negotiations were opened with North Macedonia and Albania. The EU has high expectations for Albania’s integration process: the country has demonstrated a firm commitment to accession and has consistently aligned its policies with EU guidelines. However, the enlargement reports paint a more nuanced picture, as these documents consistently criticise the functioning of the Albanian Parliament. This study examines Albania’s position within EU enlargement policy in the context of the European Commission’s annual reports, paying particular attention to parliamentary activity. Examining this dimension may provide deeper insight into the adoption of EU standards and the overall state of the enlargement process. The paper argues that parliamentary activity in Albania remains weak, effective oversight of the executive is lacking, and the substantive reforms and Europe-oriented norms required for accession are still underdeveloped.